Self-Assembly Dipeptide Hydrogel: The Structures and Properties - Li, Liangchun; Xie, Li; Zheng, Renlin; Sun, Rongqin (Frontiers in Chemistry, 2021)
Self-assembly peptide-based hydrogels are well known and attractive due to their readily controllable and biocompatibility properties in biomedical applications. Dipeptide is the shortest self-assembling motif of peptides. Due to its small size and simple synthesis method, dipeptide can provide a simple and easy-to-use method to study the mechanism of peptides self-assembly. This review describes the design and structures of self-assembly linear dipeptide hydrogels. The strategies for preparing the new generation of linear dipeptide hydrogels can be divided into three categories based on the modification site of dipeptide: (i) COOH-terminal and N-terminal modified dipeptide, (ii) C-terminal modified dipeptide, (iii)uncapped dipeptide. With the deep understanding of the relationship about structures and properties of dipeptides, we believe that dipeptide hydrogels have great potential application for the preparation of biocompatible minimal materials.